Use of SPY Elite Fluorescence Imaging in Creation of a Continent Urinary Diversion. (9th December 2019) - Hajiran, Ali; Zekan, David; Trump, Tyler; Dangerfield, Dylan; Luchey, Adam
Abstract : The use of SPY Elite Fluorescence Imaging has recently grown popular among multiple surgical specialties, including colorectal, plastic, endocrine, ophthalmologic, and vascular surgery, due to its ability to quickly and accurately assess tissue perfusion and guide intraoperative decision making. To our knowledge, the use of SPY imaging in urologic reconstructive surgery has yet to be reported. We present a case in which SPY imaging was used intraoperatively to assess perfusion of an ileocecal anastomosis and a segment of bowel prior to creation of a continent urinary diversion following radical cystectomy.